2013
DOI: 10.3109/14767058.2013.773306
|View full text |Cite
|
Sign up to set email alerts
|

The study of fetal neurobehavior in twins in all three trimesters of pregnancy

Abstract: Two types of activities were observed: spontaneous and reactive. Although twins showed less activity and different behavioral pattern than singletons, a considerable proportion of overall motility was due to intertwin contacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Twins showed different behavioural pattern than singletons with less activity and a part of the overall motility was due to inter-twin contacts [30]. The different behavioural pattern of the twins does not translate into brain pathology but maybe into a different reaction to a different environment than singletons.…”
Section: Type Of Movementmentioning
confidence: 89%
“…Twins showed different behavioural pattern than singletons with less activity and a part of the overall motility was due to inter-twin contacts [30]. The different behavioural pattern of the twins does not translate into brain pathology but maybe into a different reaction to a different environment than singletons.…”
Section: Type Of Movementmentioning
confidence: 89%
“…8 The mean timing for touch but no reaction, first reaction and slow body movements was 91 postmenstrual days (13 weeks), that for fast body movements was 92 postmenstrual days (13 weeks and 1 day), and that for more complex contacts was between 93 and 95 postmenstrual days (13 weeks and 2 days to 13 weeks and 4 days). 13 Moreover, diffuse interactions were noticed more often among fetuses between 13 and 16 weeks of gestation. 13 Interestingly, Castiello et al 1 suggested that movements toward the co-twin are not accidental: already starting from the 14th week of gestation, twin fetuses execute movements specifically aimed at the co-twin.…”
Section: Inter-twin Contact and Intra-pair Stimulationmentioning
confidence: 99%
“…13 Moreover, diffuse interactions were noticed more often among fetuses between 13 and 16 weeks of gestation. 13 Interestingly, Castiello et al 1 suggested that movements toward the co-twin are not accidental: already starting from the 14th week of gestation, twin fetuses execute movements specifically aimed at the co-twin.…”
Section: Inter-twin Contact and Intra-pair Stimulationmentioning
confidence: 99%
See 2 more Smart Citations